Determining the vertical and areal distribution of the composition of volatile oil and/or gas condensate in the reservoir - Santos Santos, Nicolás; Ortiz Cancino, Olga Patricia; Barrios Ortiz, Wilson (CT&F - Ciencia, Tecnología y Futuro, 2005)
The compositional variation in vertical and areal direction due to gravitational and thermal effects, plays an important role in the determination of the original reserves in-situ and in the selection of the operation scheme for volatile oil and/or gas condensate reservoirs. In this work we presented the mathematical formulation of the thermodynamic behavior experienced by compositional fluids, such as volatile oil and/or gas condensate, under the influence of the mentioned effects (gravitational and thermal), which was implemented in a software tool, this tool determine the compositional variation in vertical direction and, in addition, it allows to know the saturation pressure variation in the hydrocarbon column and the location of the gas-oil contact. With the obtained results, product of the use of this tool, was developed a methodology to obtain one first approach of the compositional variation in areal direction to obtain compositional spatial distribution (isocomposition maps) in the reservoir, for components like the methane, which experiences the greater variations. These isocomposition maps allow to determine the location of the hydrocarbon deposits, in such a way that the production strategies can be selected and be applied to maximize the recovery, such as infill wells, perforation of new zones, EOR processes, etc.